2009
DOI: 10.1242/jeb.028621
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SYWKQCAFNAVSCFamide: a broadly conserved crustacean C-type allatostatin-like peptide with both neuromodulatory and cardioactive properties

Abstract: SUMMARYThe allatostatins comprise three structurally distinct peptide families that regulate juvenile hormone production by the insect corpora allata. A-type family members contain the C-terminal motif -YXFGLamide and have been found in species from numerous arthropod taxa. Members of the B-type family exhibit a -WX 6 Wamide C-terminus and, like the A-type peptides, appear to be broadly conserved within the Arthropoda. By contrast, members of the C-type family, typified by the unblocked C-terminus -PISCF, a py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 48 publications
1
72
0
Order By: Relevance
“…Mercier and Russenes, 1992;Wilkens et al, 2005;Cruz-BermĂșdez et al, 2006;Cruz-BermĂșdez and Marder, 2007;Dickinson et al, 2007;Fort et al, 2007a;Fort et al, 2007b;Christie et al, 2008b;Dickinson et al, 2009). As described earlier, one H. americanus tissue in which CLDH message was detected is the CG, which controls the rhythmic beating of the heart.…”
Section: Homam-cldh Is a Potent Modulator Of Cardiac Outputmentioning
confidence: 67%
See 3 more Smart Citations
“…Mercier and Russenes, 1992;Wilkens et al, 2005;Cruz-BermĂșdez et al, 2006;Cruz-BermĂșdez and Marder, 2007;Dickinson et al, 2007;Fort et al, 2007a;Fort et al, 2007b;Christie et al, 2008b;Dickinson et al, 2009). As described earlier, one H. americanus tissue in which CLDH message was detected is the CG, which controls the rhythmic beating of the heart.…”
Section: Homam-cldh Is a Potent Modulator Of Cardiac Outputmentioning
confidence: 67%
“…In contrast, the finding of Homam-prepro-CLDH message in the CG was surprising; although the cardiac motor pattern is known to be extensively modulated by peptide hormones (e.g. Mercier and Russenes, 1992;Wilkens et al, 2005;Cruz-BermĂșdez et al, 2006;Cruz-BermĂșdez and Marder, 2007;Dickinson et al, 2007;Fort et al, 2007a;Fort et al, 2007b;Christie et al, 2008b;Dickinson et al, 2009), no peptides have been identified within the ganglion itself. By dividing the CG into pacemaker neuron-and motor neuron-specific regions, we were able to localize the production of the CLDH transcript to the latter cell type.…”
Section: The Distribution Of Calcitonin-like Diuretic Hormone Mrna Sumentioning
confidence: 92%
See 2 more Smart Citations
“…Christie, 2008a;Christie, 2008b;Christie et al, 2008;Dickinson et al, 2009;Gard et al, 2009;Ma et al, 2009a;Christie et al, 2010b;Christie et al, 2010c;Ma et al, 2010;Stemmler et al, 2010). Specifically, nucleotide sequences were translated using the Translate tool of ExPASy [Swiss Institute of Bioinformatics, Basel, Switzerland; http://www.expasy.ch/tools/dna.html (Gasteiger et al, 2003)].…”
Section: Peptide Predictionmentioning
confidence: 99%